The Impact of Problem Based Learning Model with Android Multimedia Integrated on Student Learning Outcomes and Interest - Mhd. Sholeh Kurniawan Nasution; Zainudin Muchtar; Niar Rehulina (UNDIKMA, 2023)
The implementation of a learning model and learning media in the classroom has a significant impact on learning outcomes. This research aims to assess the degree to which different educational media can influence academic outcomes and interest learn. The selected research design is the Pretest-Posttest Design. This study employs a quasi-experimental research design utilizing a nonequivalent control group. The study employs a research design that utilizes a 3x2 Factorial Design. Using SPSS 25.0 for statistical analysis, it was determined that the academic performance of students instructed through various learning models resulted in a statistically significant outcome of 0.003 α (0.05). The alternative hypothesis (Ha) was deemed acceptable, whereas the null hypothesis (H0) was deemed unacceptable. The aforementioned suggests a significant disparity in the average academic performance outcome among XI students subjected to diverse educational materials about acid-base titration. The calculated average discrepancy in academic outcome among the two groups of students is 8.61. The first experimental group, which utilized Smart Apps Creator as a learning medium and catered to various learning styles, yielded an average student learning outcome of 88.61 ± 7.98. By comparison, the mean learning outcome score for students in the second experimental class (which utilized PowerPoint as a learning medium) is 80.00 ± 7.00.